2016
DOI: 10.1093/pasj/psw022
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent cosmic ray reacceleration and the curved radio spectrum of the radio relic in the Sausage Cluster

Abstract: It has often been thought that the northern radio relic in the galaxy cluster CIZA J2242.8+5301 (the "Sausage" Cluster) is associated with cosmic ray (CR) electrons that are accelerated at a shock through the diffusive shock acceleration (DSA) mechanism. However, recent radio observations have shown that the radio spectrum is curved, which is inconsistent with the prediction of a simple DSA model. Moreover, the CR electron spectrum before being affected by radiative cooling seems to be too hard for DSA. In thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Such a phenomenon is observed in SNRs (van Adelsberg et al 2008;Yamaguchi et al 2014;Vink et al 2015) -Clumpiness and inhomogeneities in the ICM (Nagai & Lau 2011;Simionescu et al 2011), which will lead to nonlinearity of the shock-acceleration efficiency (Hoeft & Brüggen 2007) -pre-existing low-energy relativistic electrons and/or reaccelerated electrons, resulting in a flat radio spectrum with a rather small temperature jump (Markevitch et al 2005;Kang et al 2012;Pinzke et al 2013;Stroe et al 2016) -a nonuniform Mach number as a results of inhomogeneities in the ICM, which is expected in the periphery of the cluster (Nagai & Lau 2011;Simionescu et al 2011;Mazzotta et al 2011). -shock-drift accelerations, suggested from particle-in-cell simulations (Guo et al 2014a,b) -other mechanisms, for instance turbulence accelerations (e.g., Fujita et al 2015Fujita et al , 2016 Based on our X-ray observational results, we discuss some of the above possibilities.…”
Section: Possible Scenarios For the Discrepancymentioning
confidence: 74%
“…Such a phenomenon is observed in SNRs (van Adelsberg et al 2008;Yamaguchi et al 2014;Vink et al 2015) -Clumpiness and inhomogeneities in the ICM (Nagai & Lau 2011;Simionescu et al 2011), which will lead to nonlinearity of the shock-acceleration efficiency (Hoeft & Brüggen 2007) -pre-existing low-energy relativistic electrons and/or reaccelerated electrons, resulting in a flat radio spectrum with a rather small temperature jump (Markevitch et al 2005;Kang et al 2012;Pinzke et al 2013;Stroe et al 2016) -a nonuniform Mach number as a results of inhomogeneities in the ICM, which is expected in the periphery of the cluster (Nagai & Lau 2011;Simionescu et al 2011;Mazzotta et al 2011). -shock-drift accelerations, suggested from particle-in-cell simulations (Guo et al 2014a,b) -other mechanisms, for instance turbulence accelerations (e.g., Fujita et al 2015Fujita et al , 2016 Based on our X-ray observational results, we discuss some of the above possibilities.…”
Section: Possible Scenarios For the Discrepancymentioning
confidence: 74%
“…Several solutions have been proposed to solve this problem using the northern relic in CIZA J2242.8+5301 as a prototype. Kang & Ryu (2016, 2015 proposed that fossil electrons (accelerated by the DSA mechanism) are reaccelerated as the shock runs them over; Fujita et al (2016) suggested that cosmic rays are reaccelerated by turbulence generated behind shocks; Donnert et al (2016) offered another explanation: magnetic turbulence generated by the amplification of the magnetic field is responsi- ble for the particle reacceleration. An alternative solution was suggested by : the curved radio spectrum is a consequence of the SZ effect, which lowers the measured radio flux at the observed radio wavelengths (< 217 GHz).…”
Section: Ciza J22428+5301: a Merging Cluster With The Prototype Of Re...mentioning
confidence: 99%
“…Note that the collision axis is also aligned vertically, as in Figure 3. lision is close to the plane of the sky), have been used to test different particle acceleration models, e.g., DSA mechanism (Stroe et al 2016, also analyzed 1RXS J0603.3+4214, the "Toothbrush" cluster); fossil electrons (accelerated by the DSA mechanism) are reaccelerated as the shock runs them over (Kang & Ryu 2015); turbulent cosmic ray reacceleration (Fujita et al 2016); and magnetic turbulence generated by the amplification of the magnetic field (Donnert et al 2016).…”
Section: Bias In Mach Numbers Derived From X-ray Observationsmentioning
confidence: 99%
“…The lack of connection between radio relics and shocks in several merging clusters, together with the low efficiency of DSA for M ∼ 2-3 of these shocks, seems to suggest that in some cases the DSA assumption is not enough for the electron acceleration from the thermal pool (Vink & Yamazaki 2014;Vazza & Brüggen 2014;Skillman et al 2013;Pinzke et al 2013). For this reason, alternative mechanisms have been proposed recently, as for example the re-acceleration of pre-existing cosmic ray electrons (Markevitch et al 2005;Kang et al 2012;Fujita et al 2015;Fujita et al 2016;Kang 2017) and shock drift acceleration (Guo et al 2014a(Guo et al ,b, 2017. However, it is not clear what type of mechanism is involved and whether all relics need additional mechanisms or not.…”
Section: Introductionmentioning
confidence: 99%